A comparison study of GeneXpert and In-House N1N2 CDC Real-Time RT-PCR for detection of SARS-CoV-2 infection - Andi Yasmon; Lola Febriana Dewi; Fithriyah Fithriyah; Ariyani Kiranasari; Andriansjah Rukmana; Yulia Rosa Saharman; Fera Ibrahim; Pratiwi Sudarmono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
COVID-19 is a disease caused by SARS-CoV-2, a new virus from genus β-coronaviruses. This disease has been declared a pandemic by WHO on 11 March 2020 until now. The nucleic acid tests are the most frequently used assays because of their high sensitivity and specificity. One of the tests is the GeneXpert, a real-time reverse transcription polymerase chain reaction (rRT-PCR)-based assay platform. The use of the GeneXpert shows great public health interest because of the rapid (50 min), the minimum number of trained staff, and less infrastructure and equipment. However, there are limited data on the application of the GeneXpert for the detection of SARS-CoV-2. Therefore, we conducted a comparative study between the GeneXpert and in-house N1N2 CDC rRT-PCR assay. Of 86 samples, 17 were rRT-PCR positive while 13 were GeneXpert positive. Of rRT-PCR positive 17 samples, 7 were GeneXpert negative [58.82% (10/17] sensitivity]. We also found that 3 GeneXpert positive samples showed rRT-PCR negative (95.65% [66/69] specificity). It is concluded that negative results by the GeneXpert can not rule out the possibility of SARS-CoV-2 infection, particularly in close-contact individuals and the interpretation of the positive result should be analyzed carefully, particularly amplification with Ct>40.